From behavioral inhibition in toddlers to anxiety disorder: Influencing factors - Monteiro, Maria do Rosário; Rodrigues, Márcia; Martins, Vânia (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Behavioral inhibition (BI), a biologically driven temperamental trait defined by fearful, avoidant, and withdrawn reactions to novelty, is known to represent an early vulnerability in the development of anxiety disorders. Herein is reported the case of two 18-month-old twins whose parents exhibited high levels of anxiety, restricting the infants’ exposure to new stimuli and experiences. One of the twins exhibited inhibited behaviors with high physiological activation and met criteria for inhibition to novelty disorder. Several factors may predict the persistence of BI across the lifespan and moderate its association with later anxiety disorders, including cognitive or attentional biases, variations in neural functioning, attachment processes, parental psychopathology, and parenting practices. The COVID-19 pandemic exacerbated parental anxiety and pre-existing risk factors in particularly vulnerable children.